A Comparative Study on the Efficacy of Diperoxochloric Acid Solution Versus Normal Saline in the Management of Diabetic Foot Ulcers - Sajin. J, Joseph; Sajin. J, Joseph; P, Ragumani (Journal of Neonatal Surgery, 2025)
Background: Diabetic foot ulcers (DFUs) are a debilitating complication of diabetes, affecting 15% of individuals with diabetes during their lifetime. They contribute significantly to morbidity, mortality, and healthcare costs. Current treatments for DFUs include saline dressings, which often show limited efficacy. Diperoxochloric acid (DPOCL), a novel topical solution, combines antimicrobial properties with fibroblast-proliferating action, making it a promising alternative in DFU management. Materials and Methods: This prospective, randomized, controlled study was conducted on 80 patients with type 2 diabetes and full-thickness DFUs. Patients were randomized into two groups: DPOCL Group: Dressings with DPOCL solution. Control Group: Dressings with normal saline.Both groups received standard care, including glycemic control, systemic antibiotics, offloading, and sharp debridement. The primary outcome was the percentage reduction in wound surface area over four weeks. Secondary outcomes included time to complete wound closure, quality of granulation tissue formation, and incidence of adverse events. Data were analyzed using SPSS software, and a p-value <0.05 was considered statistically significant. Results: The DPOCL group exhibited a significantly greater mean percentage reduction in wound surface area (68.4% ± 11.2%) compared to the saline group (42.7% ± 9.8%, p < 0.001). The mean time to complete wound closure was shorter in the DPOCL group (21.6 ± 5.3 days) than the saline group (31.8 ± 6.4 days, p < 0.001). By the second week, 87.5% of DPOCL-treated patients showed robust granulation tissue formation versus 62.5% in the saline group (p = 0.012). Adverse events were mild and comparable between groups (DPOCL: 5%, Saline: 7.5%, p = 0.72). Conclusion: DPOCL solution significantly accelerates wound healing, enhances granulation tissue formation, and effectively controls infections in DFUs compared to normal saline. Its favorable safety profile and efficacy make it a promising alternative in DFU management. Future multicenter trials are recommended to validate these findings and explore broader applications